Dictionary of media and communication studies - Watson, James, 1936-; Hill, Anne, 1952- (Bloomsbury Academic, 2015)
The Dictionary of Media and Communication Studies has provided students and the general public alike with a gateway into the study of intercultural communication, public relations and marketing communications since 1984. In this 9th edition, James Watson and Anne Hill provide a detailed compendium of the different facets of personal, group, mass-media and internet communication that continues to be a vital source of information for all those interested in how communication affects our lives.- Resumé vydavatel
Keywords: komunikace (sdělování); sociální komunikace; mediální komunikace; communication; human communication; communication in mass media; elektronické knihy; výkladové slovníky; electronic books; explanatory dictionaries